Câu 2:
(m - 2)x^2 - 2(m - 4)x - 2 = 0 (1)
Δ' = m^2 - 8m + 16 + 2(m - 2)
= m^2 - 6m + 12
Theo Viet: S = x1 + x2 = 2(m - 4)/(m - 2)
P = x1x2 = -2/(m - 2)
a) (1) có 2 nghiệm trái dấu <=> a # 0 và Δ' ≥ 0 và P < 0
<=> m - 2 # 0 và m^2 - 6m + 12 ≥ 0, ∀m và -2(m - 2) < 0
<=> m # 0 và m > 2 <=> m > 2
Vậy...
b) (1) có 2 nghiệm pb <=> a # 0 và Δ' > 0
<=> m # 2 và m^2 - 6m + 12 > 0, ∀m
<=> m # 2
Ta có: x1 - x2 = 3 => x1 = 3 + x2
Thế x1 = 3 + x2 vào S: 2x2 = (2m - 8 - 3(m - 2))/(m - 2)
<=> 2x2 = (-m - 2)/(m - 2)
<=> x2 = (- m - 2)/(2m - 4)
=> x1 = 3 + (-m - 2)/(2m - 4)
<=> x1 = (6m - 12 - m - 2)/(2m - 4) = (5m - 14)/(2m - 4)
Thế x1 = (5m - 14)/(2m - 4) và x2 = (-m - 2)/(m - 2) vào P:
(5m - 14)(- m - 2) = -2(2m - 4) (đk: m # 2)
<=> - 5m^2 - 10m + 14m + 28 = - 4m + 8
<=> 5m^2 - 8m - 20 = 0
<=> m = (4 ± 2√29)/5 (nhận)
Vậy...